2018
DOI: 10.1111/puar.12953
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Institutional Arrangements Shape Stakeholder Influence on Policy Decisions: A Comparative Analysis in the Energy Sector

Abstract: In recent years, there has been an expansion of efforts to include stakeholders in administrative policy making. Despite significant potential to improve policy decisions, empirical evidence suggests that not all participatory processes provide meaningful opportunities for stakeholders to shape policy and may even give the most powerful stakeholder groups disproportionate influence over policy decisions. This article argues that the institutional arrangements for stakeholder engagement-the rules and norms that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
4
11
0
Order By: Relevance
“…Furthermore, we found that by-district COA governance reduces racial disparity in DCAs, which shows that institutional rules for stakeholder engagement in participatory processes affect stakeholders' influence on policy outcomes. This result adds to the prior finding in the literature that stakeholder engagement in participatory processes enhances stakeholder influence on policy decisions (Baldwin 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, we found that by-district COA governance reduces racial disparity in DCAs, which shows that institutional rules for stakeholder engagement in participatory processes affect stakeholders' influence on policy outcomes. This result adds to the prior finding in the literature that stakeholder engagement in participatory processes enhances stakeholder influence on policy decisions (Baldwin 2019).…”
Section: Discussionsupporting
confidence: 79%
“…The participation of biofuel producers, fossil producers and distributors as obligated parties is noted. These observations are in accordance with previous literature, which indicates that in many processes where there is primarily participation by stakeholders directly involved in the regulated industry, there may be limited political impact or the impact may favor those who participated to the detriment of the public interest (CROW; ALBRIGHT; KOEBALE, 2017;BALDWIN , 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Although replicating studies in different national contexts has a long history in psychology (see Rokeach and the seminal work of Hofstede ), spawning an entire field of cultural psychology (Kitayama and Cohen ; applied to organizations, see Smith, Peterson, and Schwartz ), public administration scholarship is just beginning such work. First, there is some evidence that generic macro factors such as unemployment (Olsen ), the state of the economy (Powell and Whitten ; Singer ), organizational past performance (Olsen ), the performance of others (Charbonneau and Van Ryzin ), institutional logics (Ngoye, Sierra, and Ysa ), institutional arrangements (Baldwin ), and social capital (Beugelsdijk and Van Schaik ) influence individual attitudes and behaviors.…”
Section: Public Administration As a Design Sciencementioning
confidence: 99%